A rede do café: Diálogos espaço-tempo para identificação das fazendas cafeeiras na Zona da Mata mineira - Fernanda de Oliveira Silva Portela (2019)
The elaboration of this research was based on the existence of gap, from the point of view of the production of knowledge in the field of architecture, and in the recognition by the preservation organs in terms of identification of the nineteenth century coffee farms in the “Zona da Mata mineira”. Although coffee expansion into the “Zona da Mata” was part of a broader process in the Paraíba do Sul hydrographic basin, as a consequence of the development of the Paraíba Paulista valley and the Fluminense region crops, there was a difference in the treatment of these objects, where, for comparative analysis, there was a certain neglect concerning the Minas Gerais part, which are in a current worrying scenario, with the lack of adequate policies for their preservation, constantly being the target of mischaracterization, abandonment, or even destruction, without there are records about its existence. In this sense, the research that supported the preparation of this work aimed to find ways to identify the coffee specimens, highlighting the existence of this gap in the Minas Gerais area and proposing a new look at the construction of its historiography, in order to demonstrate the importance of the “Zona da Mata Mineira”, reinserting it in the discourse of coffee expansion. In this process it was necessary to adopt two spatial cuttings, starting from a macro scale (considering the limits of the Paraíba do Sul hydrographic basin) to understand the phenomenon of coffee expansion, until reaching the micro scale (Juiz de Fora) to make possible a closer approximation to the object, taking for both the period between the late eighteenth century and the first decades of the twentieth century. The methodological construction of the work was based on a process of archaeological bias, where we abandoned the concept of a thread for the narrative and thought of time-space overlaps to find the objects. The facts were presented and structured in layers, as if we were building a drawing, and they are gradually dissected and approximated until we can find the coffee specimens.